Botrytis Blight of Syzygium cumini Skeels in India - Khan, S. N.; Misra, B. M. (Indian Forester, 1996)
Grey mould blight of Syzygium cumini caused by Botrytis cinerea is reported from India. Symptoms, epidemiology and disease management are discussed briefly.